GANGLION IMPAR BLOCK FOR CHRONIC COCCYDYNIA - Malik, Sara Haider; Khaleel Ahmad,; Liaquat Ali, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Coccydynia is also known as coccygodynia or coccygeal neuralgia. Coccyx is a triangular bone located within the vertebral column. The cause of coccydynia is unknown in the literature; however, it is found to be common among obese individuals, particularly females. The probability of women having coccydynia is five times higher than among men, which may result from larger pressure during pregnancy and child delivery. It is treated well with ganglion impar block. The aim of our study was to assess pain relief after Ganglion Impair Block with subsequent improvement in quality of life. Methods: A single-arm study was done in the department of Pain Medicine, Fauji Foundation Hospital, Rawalpindi from July 2021 to June 2022. A total of 50 patients with ‰¥3 months coccygeal pain of either gender aged between 20-60 years unresponsive to analgesics & anti-inflammatory medications with no laboratory abnormalities were included. Fluoroscopic guided trans-sacro'‘coccygeal ganglion impair block was done with alcohol neurolysis. The patients were observed for 1 hour in the recovery room to record post-intervention complications that may occur like hypotension, bradycardia, signs, and symptoms of cardiotoxicity or neurotoxicity etc. and evaluated for pain scores on the basis of the numeric rating scale (NRS). Data collected was analyzed using the statistical package for social scientists (SPSS) version 21. The quantitative data, i.e., age and NRS score were analyzed using mean and standard deviation and compared between pre and post-intervention periods. Results: The data from 50 patients who completed the follow-up period were used for analysis. The average age of the patients was 42.9±8.39 years, with a range of 38-60 years. Based on the data obtained, 30% of the patients experienced trauma (that is falling on the coccyx region). The mean score from NRS before intervention was 7.80±0.16 which decreased to 0.96±0.35, respectively, and this difference was statistically significant (p-value, <0.001). Conclusions: Ganglion Impar neurolysis is highly effective in the treatment of Chronic coccydynia.